(untitled) (Journal of Oriental Studies, 2026)
The aim of this article is to identify the specific features and limits of the reform programs of Şahin Giray, the last Crimean khan, and Jaŋgir Khan of the Inner (Bökey) Horde by comparing them with the modernization trajectories of Meiji Japan, China’s Self-Strengthening Movement, and Korea’s reforms (Gabo and Gwangmu). Using a comparative historical approach, the article demonstrates that, despite a shared rhetoric of “renewal” and “enlightenment,” steppe reforms unfolded under fundamentally different conditions of constrained sovereignty and colonial pressure. Whereas in Japan modernization functioned as a strategy for strengthening an independent state, Şahin Giray and Jaŋgir Khan were compelled to pursue a form of “colonial modernization,” embedded within Ottoman and Russian imperial frameworks and limited by the dependent status of their polities. Particular attention is paid to the social bases of reform, patterns of elite support, and sources of resistance – from Nogai-Tatar elites and Crimean society to Kazakh uprisings against Jaŋgir Khan. The aim of the study is to identify the features and limitations of “colonial modernization” in the steppe, as well as the forms of socio-political resistance, through a comparative analysis of the reforms of Jangir Khan and Shahin Giray alongside modernization processes in Japan, China, and Korea. The practical significance of the study lies in refining comparative criteria for analyzing “late Eastern” modernizations; the findings may be used in designing university courses on reform and colonial transformation and in preparing synthetic studies on the histories of the Crimean Khanate, the Kazakh steppe, and East Asia. The article concludes that steppe reforms were not a “failed copy” of East Asian modernizations but a distinctive strategy of survival and adaptation within an imperial order, requiring a reassessment of binary notions of “successful” versus “unsuccessful” modernization. Keywords: Zhangir Khan, Bukey Horde, Kazakh steppe, Isatay Taymanuly, Makhambet Otemisuly, reforms, Meiji era.